Princess Vlei : what diatoms can tell us about spatial and temporal heterogeneity in an urban wetland - Cowan, Oliver (Department of Biological Sciences, 2017)
Globally, wetlands are being degraded and destroyed largely as a result of anthropogenic activity. Monitoring and assessment are required to maintain functional ecosystems and the valuable services they provide. Surface sediment cores were taken from 4 points around an urban wetland (Princess Vlei) on the Cape Flats, Cape Town, South Africa. Diatoms were and used as a proxy for water quality variables to determine whether the diatom flora preserved in organic sediments accumulating in and around an urban wetland is a useful tool in determining the changes in water quality over time. In addition, the project attempts to establish whether there are spatial patterns in diatom flora within a small lake. Diatoms from three depths from each of the four sites were identified, counted and analyzed according to their trophic preferences and pollution tolerances which were acquired from a variety of resources. Results showed clear spatial differences between sites as a result of positioning in relation to effluent input, output and specific site characteristics such as reed stands. Differences between depths were evident although no significant trends were observed. In summation; spatial heterogeneity in the diatom assemblage of an urban wetland reveal that diatoms are suitable indicators of water quality, even within a small system, due to their niche specificity. The project also shows that Princess Vlei remains a eutrophic and polluted wetland, although not uniformly so. Continual monitoring is required to prevent the vlei from becoming a health hazard for the surrounding community and to maintain its ability to act as a buffering zone to protect the Rondevlei nature reserve, as well as acting as a functional ecosystem in an area threatened by urbanization.